Ganea Peter y Thomas Pattloch, Intellectual Property Law in China, La Haya, Wolters Kluwer, 2005, 2088 pp. - Juárez Aguilar, María Beatriz (Estudios de Asia y África, 2007)
Ganea Peter y Thomas Pattloch, Intellectual Property Law in China, La Haya, Wolters Kluwer, 2005, 2088 pp.